2010
DOI: 10.1093/nar/gkq349
|View full text |Cite
|
Sign up to set email alerts
|

Rapid decay of unstable Leishmania mRNAs bearing a conserved retroposon signature 3′-UTR motif is initiated by a site-specific endonucleolytic cleavage without prior deadenylation

Abstract: We have previously shown that the Leishmania genome possess two widespread families of extinct retroposons termed Short Interspersed DEgenerated Retroposons (SIDER1/2) that play a role in post-transcriptional regulation. Moreover, we have demonstrated that SIDER2 retroposons promote mRNA degradation. Here we provide new insights into the mechanism by which unstable Leishmania mRNAs harboring a SIDER2 retroposon in their 3′-untranslated region are degraded. We show that, unlike most eukaryotic transcripts, SIDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(65 citation statements)
references
References 66 publications
5
60
0
Order By: Relevance
“…As we have reported previously, SIDER2 retroposon promotes rapid RNA decay, whereas deletion of SIDER2 from the 3 ′ UTR blocks degradation and causes accumulation of the LUC reporter mRNA ( Fig. 1D; Bringaud et al 2007;Müller et al 2010b). Here, we show that addition of two MS2 hairpins in the reporter RNA and binding to MCP does not alter degradation by SIDER2 (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…As we have reported previously, SIDER2 retroposon promotes rapid RNA decay, whereas deletion of SIDER2 from the 3 ′ UTR blocks degradation and causes accumulation of the LUC reporter mRNA ( Fig. 1D; Bringaud et al 2007;Müller et al 2010b). Here, we show that addition of two MS2 hairpins in the reporter RNA and binding to MCP does not alter degradation by SIDER2 (Fig.…”
Section: Resultssupporting
confidence: 79%
“…In addition, gene expression has been shown to change dramatically throughout the complex life cycles of these parasites (Haile and Papadopoulou 2007;Rochette et al 2008;Nilsson et al 2010;Siegel et al 2010). Regulation of mRNA decay rates through interactions of RNA-binding proteins (RBPs) with cis-acting sequences in 3 ′ UTRs of trypanosomatid transcripts is central in determining the fate of mRNAs and thus fine-tuning developmental gene expression (McNicoll et al 2005;Bringaud et al 2007;Haile and Papadopoulou 2007;Haile et al 2008;Müller et al 2010b;Kramer 2012;Clayton 2013). Several RBPs, such as zinc finger proteins, Alba-domain proteins, and Pumilio (PUF) proteins, have been found to regulate mRNA stability in trypanosomatids (Clayton 2013;Dupé et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An identical mechanism was considered for the fast decay of EP1 mRNA in bloodstream form T. brucei [26], but this was not confirmed by a subsequent study [28]. However, degradation of unstable Leishmania transcripts bearing a retroposon-derived instability motif in their 3 UTR appears to be initiated by endonucleolytic cleavages at discrete sites [48]. We identified 9 different 3 ends within the GPEET 3 UTR (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Instead, these protein-coding genes are constitutively transcribed from large gene clusters, and steady state levels of their mature mRNAs are regulated post-transcriptionally by trans-splicing and polyadenylation (Kramer 2012 ;Haile and Papadopoulou 2007). Several studies reported that posttranscriptional regulation of developmentally expressed transcripts in Leishmania species involves sequences present mainly in the 3'-UTR (Muller et al, 2010 ;Boucher et al, 2002;McNicoll et al, 2005;Bringaud et al, 2007), but also in the 5'UTR Lamontagne and Papadopoulou 1999) and in intergenic regions between tandemly repeated genes (Ramamoorthy et al, 1995;Beetham et al, 1997). Logarithmic-stationary gene regulation is also regulated by 3'-UTR (Myung et al, 2002).…”
Section: Introductionmentioning
confidence: 99%